The worst thing I've done : a novel - Hegi, Ursula (Simon and Schuster, 2007)
Electing to raise her infant sister when her parents are killed on her wedding day, Annie finds her intimate friendships with Jake and Mason tested until a fateful night during which the three companions goad each other into crossing a dangerous line.